Phospholipid remodeling and its derivatives are associated with COVID-19 severity - Wei, Juntong; Liu, Xiaoyu; Xiao, Weimin; Lu, Jiahua; Guan, Li; Fang, Zhangfu; Chen, Jiaping; Sun, Baoqing; Cai, Zongwei; Sun, Xizhuo; Chen, Hua-Ling; Zhong, Nanshan; et al. (Journal of allergy and clinical immunology, 2023)
[Display omitted] Timely medical intervention in severe cases of coronavirus disease 2019 (COVID-19) and better understanding of the disease’s pathogenesis are essential for reducing mortality, but early classification of severe cases and its progression is challenging. We investigated the levels of circulating phospholipid metabolites and their relationship with COVID-19 severity, as well as the potential role of phospholipids in disease progression. We performed nontargeted lipidomic analysis of plasma samples (n = 150) collected from COVID-19 patients (n = 46) with 3 levels of disease severity, healthy individuals, and subjects with metabolic disease. Phospholipid metabolism was significantly altered in COVID-19 patients. Results of a panel of phosphatidylcholine (PC) and lysophosphatidylcholine (LPC) and of phosphatidylethanolamine and lysophosphatidylethanolamine (LPE) ratios were significantly correlated with COVID-19 severity, in which 16 phospholipid ratios were shown to distinguish between patients with severe disease, mild disease, and healthy controls, 9 of which were at variance with those in subjects with metabolic disease. In particular, relatively lower ratios of circulating (PC16:1/22:6)/LPC 16:1 and (PE18:1/22:6)/LPE 18:1 were the most indicative of severe COVID-19. The elevation of levels of LPC 16:1 and LPE 18:1 contributed to the changes of related lipid ratios. An exploratory functional study of LPC 16:1 and LPE 18:1 demonstrated their ability in causing membrane perturbation, increased intracellular calcium, cytokines, and apoptosis in cellular models. Significant Lands cycle remodeling is present in patients with severe COVID-19, suggesting a potential utility of selective phospholipids with functional consequences in evaluating COVID-19’s severity and pathogenesis.